A fractal theory approach to the initial examination of normal faulting in Central Corinthian Gulf, Greece - KONDYLAKIS, J.C.; PAPOULIA, J.E. (Mediterranean Marine Science, 2001)
An application of fractal theory in geological formations in the central Corinthian Gulf, Greece, is presented in an attempt to study the nature of presently active deformation. Fault patterns are approximated under the perspective of fractal theory concept, leading to the conclusion that fractal approach can be considered valid for the region of study. Nevertheless, homogeneity may be expected with the reservation that there are no considerable changes in the viscosities of the ductile layers in the region, so that the characteristic exponent b+1-a is less than zero.